BINOL diesters as useful building blocks towards chiral macrocyclic compounds. Issue 16 (21st April 2016) - Pikus, Grzegorz; Jurczak, Janusz
Abstract: Double-amidation reaction of ( R )- or ( S )-2, 2′-([1, 1′-binaphthalene]-2, 2′-diylbis(oxy))diacetic dimethyl ester with five differing in length α, ω-diaminoethers were used for the synthesis of chiral macrocyclic compounds of different size of the cavity, potential receptors of various chiral guests. Graphical abstract: